PERANCANGAN APLIKASI PENILAIAN KINERJA KEPALA LINGKUNGAN KECAMATAN MEDAN HELVETIA DENGAN METODE GRS & 360 DEGREES BERBASIS ANDROID - Tarigan, Feriani Astuti (Universitas Methodist Indonesia, 2023)
Performance appraisal is an important part of seeing the results of each employee's work performance, including the Head of the Neighborhood who is the spearhead of Government services to the community. However, the Head of Neighborhood has not found a standardized performance appraisal so that the author is interested in making a performance appraisal system for the Head of Neighborhood, especially in Medan Helvetia District and at the same time building an easy-to-use assessment application. This Neighborhood Head Performance Assessment Application uses a combination of the Graphic Rating Scale (GRS) algorithm to make it easier to see the assessment results and the 360 Degrees algorithm so that the assessment results are more objective. The assessment results obtained can be a recommendation for reward and punishment. The application also requires development to iOS-based smartphones so that more users can utilize it.